Water stress and temperature on germination and vigor of Handroanthus impetiginosus (Mart. ex DC) - Paulo C. S. Santos; Clarisse P. Benedito; Tatianne R. C. Alves; Emanoela P. Paiva; Erivanessa C. Sousa; Afonso L. A. Freires (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Water availability and temperature are among the main abiotic factors that influence seed germination and vigor, since they act directly on biochemical and physiological processes, which result in the production of the primary root. The objective of this study was to verify the effects of stress on germination and vigor of H. impetiginosus (‘ipê-roxo’) seeds under different temperatures and osmotic agents. The experimental design was completely randomized, in a 6 x 2 factorial scheme (osmotic potentials x temperatures) with four replicates of 25 seeds for each osmotic agent. In order to simulate water stress, polyethylene glycol (PEG 6000) and mannitol solutions were used and distilled water was used as control. Osmotic potentials of 0, -0.2, -0.4, -0.6, -0.8 and -1.0 MPa were evaluated at temperatures of 25 and 30 °C, under 8 h photoperiod. The variables analyzed were: germination, germination speed index, shoot length, root length, and total dry matter of seedlings. Simulated water stress affected seed germination and seed vigor of H. impetiginosus at both temperatures and osmotic agents from -0.6 MPa.